find and explain the error in the students work below

solve: 2m^2-7m-30=0
2m^2+5m-12m-30=0
m(2m+5)-6(2m+5)=0
(2m+5)(m-6)=0
the student states that the answers are 2m+5 and m-6

1 answer

The error in the student's work is in the distribution step when simplifying "m(2m+5)-6(2m+5)=0." The student should have distributed the -6 to both terms inside the parentheses. The correct distribution should look like this: "m(2m+5) - 6(2m+5) = 0" becomes "2m^2 + 5m - 12m - 30 = 0."

Therefore, the correct factorization should be "(2m + 5)(m - 6) = 0." The correct answers are m = -5/2 and m = 6.
Similar Questions
  1. Find and explain the error in the​ student’s work/answers below.​Solve: ​ m² + m​ – 6​ = 0 ​ m² – 2m​ +
    1. answers icon 3 answers
  2. Find and explain the error in the​ student’s work below.Solve​ 2x² - 5x​ -12 = 0 using the Quadratic Formula.
    1. answers icon 1 answer
  3. Find and explain the error in the student's work below.Solve 2t^- 5t-12=0 using the Quadratic Formula.
    1. answers icon 1 answer
  4. Find and explain the error in the student's work/answers belowSolve: m²+m-6=0 m^2-2m +3m-6=0 m(m-2)+3(m-2)=0 (m-2)(m+3) =0
    1. answers icon 1 answer
more similar questions